Motor imagery therapy improved upper limb motor function in stroke patients with hemiplegia by increasing functional connectivity of sensorimotor and cognitive networks - Liu, Wan; Cheng, Xinxin; Rao, Jiang; Yu, Jiawen; Lin, Zhiqiang; Wang, Yao; Wang, Lulu; Li, Danhui; Liu, Li; Gao, Run (Frontiers in Human Neuroscience, 2024)
Background: Motor imagery therapy (MIT) showed positive effects on upper limbs motor function. However, the mechanism by which MIT improves upper limb motor function is not fully understood. Therefore, our purpose was to investigate the changes in functional connectivity (FC) within and outside the sensorimotor network (SMN) induced by MIT. Methods: A total of 26 hemiplegic stroke patients were randomly divided into MIT (n = 13) and control (n = 13) groups. Fugl-Meyer Assessment Upper Extremity Scale (FMA-UL), Modified Barthel Index (MBI) and resting-state functional magnetic resonance imaging (rs-fMRI) were evaluated in the two groups before and after treatment. FC within the SMN and between the SMN and the whole brain was measured and compared before and after different treatment methods. The correlation analysis between the improvement of motor function and changes in FC was examined.The FCs between ipsilesional primary motor cortex (M1.I) and contralateral supplementary motor area (SMA.C), M1.I and ipsilesional SMA (SMA.I), and SMA.C and contralateral dorsolateral premotor cortex (DLPM.C) significantly increased in the control group but decreased in the MIT group; while the FC between SMA.C and contralateral primary somatosensory cortex (S1.C) significantly increased in the control group but showed no difference in the MIT group. The FCs between M1.I and the ipsilesional hippocampal gyrus and ipsilesional middle frontal gyrus decreased in the control group but increased in the MIT group; while the FC in the contralateral anterior cingulate cortex increased in the MIT group but there was no difference in the control group. The results of the correlation analysis showed that the differences in abnormal intra-FCs within the SMN negatively correlated with the differences in FMA and MBI, and the difference in abnormal inter-FCs of the SMN positively correlated with the differences in FMA and MBI.Conclusions: MIT can improve upper limb motor function, and the improvement effect of conventional rehabilitation therapy (CRT) combined with MIT is significantly higher than that of CRT alone. CRT may improve the upper limb motor function of stroke patients with hemiplegia mainly through the functional reorganization between SMN, while MIT may mainly increase the interaction between SMN and other brain networks.